Recent developments in two-dimensional layered tungsten dichalcogenides based materials for gas sensing applications. (September 2021) - Sanyal, Gopal; Vaidyanathan, Antara; Rout, Chandra Sekhar; Chakraborty, Brahmananda
Abstract: Layered transition metal dichalcogenides (2D-TMDs) are promising materials for critical applications in the fields of electronics, gas detection, energy storage and conversion, etc. Among the various TMDs, tungsten dichalcogenides i.e., WX2 (X = S, Se, Te) with tungsten (W) as the cation are exceptionally interesting due to the natural abundance of W, tuneable bandgaps for a relatively bigger cation size, enabling specialized applications such as electrocatalysis, counterion diffusion, superconductivity, etc. Ultrathin layered WX2 and its heterojunctions show enhanced gas sensing ability due to tremendous surface-to-volume ratio, active edges with atomic thickness as well as tuneable electronic and mechanical properties. This review attempts to be an exhaustive and comprehensive analysis of these WX2 compounds in terms of their properties and processing routes, with special emphasis on their potential for gas-sensing applications. The review begins with the important properties, synthesis methods of WX2 and further provides an overview of the significant achievements in its gas sensing applications for reducing and oxidizing gases, with an attention on both theoretical and practical findings. Furthermore, the strategies to achieve improved sensing performance and the future directions for practical applications are critically discussed.